ANALISIS PEMAHAMAN KONSEP TERMODINAMIKA BAGI CALON GURU FISIKA - H.Hidayat, Ekarufika; Muslimin, Muslimin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This research was conducted with the aim of reviewing, knowing and analyzing the understanding of thermodynamic concepts of prospective physics teachers in physics education study programs. The type of research used is descriptive qualitative research. The subjects of this study were students of the physics education study program at Tadulako University. Respondents in this study were 3 people. The instrument used is 3 numbers of thermodynamic essay questions accompanied by thinking aloud to determine the understanding of the respondents. In this study the matter of thermodynamics is limited only to the 1st law of thermodynamics . Based on the results of the analysis of research data obtained an average score of 8.34 concept understanding. The results showed that the students' understanding of the concept of thermodynamics was still relatively low. students are still wrong in reading graphs of thermodynamic processes.